O valor econômico agregado à sociedade (VEAS) pelo hospital universitário da UFSCar no ano de 2017 - Ramos, Virginia Ribeiro Barbosa (2019)
In the current scenario of Brazil’s Public Health, which presents many budgetary restrictions, one of the measures found by the State in order to face them is the incentive given to entities with social objectives. This context indicates the need to reflect upon the efficiency and effectiveness in the application of financial resources offered by the State to assistance institutions such as a Federal University Hospital (FUH) that, besides offering medical assistance, carries out teaching and research activities and it is considered a reference in state-of-the-art technology equipment. The present study aimed at demonstrating if the federal government investment in the University Hospital “Prof. Dr. Horácio Panepucci” of the Federal University of São Carlos (UH – UFSCar), in the year of 2017, added economic value to the society after the Brazilian Company of Hospital Services (EBSERH) has taken over the institution management. In order to do that, a case study was carried out at the institution, in which information about all the ambulatory procedures and hospitalizations was obtained, with subsequent SUS value conversions into market values, as well as the identification of all the direct and indirect costs and State investments in the entity. The results of the Economic Value Added Short Term (VECP) and the Economic Value Added to the Society (VEAS) have been positive in the considered period, which demonstrates the institution’s efficiency in using the capital invested by the State and confirming its aptitude in offering health assistance services to the community, as well as its capacity to remunerate the value opportunity cost that was entrusted to it. This study has also identified a significant difference between SUS values and market values and this led to the conclusion that, if UH – UFSCar did not exist, the society would have to pay private initiative on average 9,74 times more for hospital services. Furthermore, these results are extremely important for public management because they demonstrate, through the positive Operational Economic Result, that the institution managers have administrated public resources in an efficient way, returning the taxpayers a lower cost compared to the market, with potential to provide services that add value. The results analysis presented in this research prove the importance of using public governance as a management tool able to provide public management transparency. For these reasons, the performance assessment tools must be required by the society to obtain real information on the uses of investments made by the State.